2014
DOI: 10.1186/1471-2474-15-79
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Injury Management (AIM): design of a pragmatic multi-centre equivalence randomised controlled trial comparing Close Contact Casting (CCC) to Open surgical Reduction and Internal Fixation (ORIF) in the treatment of unstable ankle fractures in patients over 60 years

Abstract: BackgroundAnkle fractures account for 9% of all fractures with a quarter of these occurring in adults over 60 years. The short term disability and long-term consequences of this injury can be considerable. Current opinion favours open reduction and internal fixation (ORIF) over non-operative treatment (fracture manipulation and the application of a standard moulded cast) for older people. Both techniques are associated with complications but the limited published research indicates higher complication rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…There are a number of studies published on functional recovery following ankle fracture fixation. 2,8,10,11,19,24 However, there is minimal evidence of the long-term outcomes. Our study has identified that there will be a permanent significant reduction in the functional outcome following ankle fracture fixation over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of studies published on functional recovery following ankle fracture fixation. 2,8,10,11,19,24 However, there is minimal evidence of the long-term outcomes. Our study has identified that there will be a permanent significant reduction in the functional outcome following ankle fracture fixation over time.…”
Section: Discussionmentioning
confidence: 99%
“…In the Ankle Injury Management (AIM) trial, the authors reported a reduction in OMAS at 6 weeks and 6 months for patients aged >65 sustaining ankle fracture. 24 Nilsson et al 16 showed that patients aged >65 years with ankle fracture required at least 1 year to achieve similar functionality to the control group without a fracture. Egol et al 8 reported a significantly better outcome in patients aged <40 years in comparison with patients aged >40 years at the 1-year follow-up, but this was not shown by Lash et al 11 (2 years) or Belcher et al 2 (8-24 months).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the cast must be replaced or adjusted and the condition of soft tissue must be observed regularly 11 . When facing severely unstable ankle fractures, especially those with talus dislocation or subluxation, even a good cast can hardly guarantee the maintenance of reduction 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries, unstable ankle fractures typically undergo internal fixation surgery to restore normal anatomy 10. Below-knee casts are also used in older adults as they have greater risks from surgery than younger people 11. The AIM trial showed surgery and close contact casting for managing unstable ankle fractures in older adults had equivalence in functional outcomes 9.…”
Section: Introductionmentioning
confidence: 99%